The red island and the seven dwarfs: body size reduction in Cheirogaleidae. (14th July 2014) - Masters, Judith C.; Génin, Fabien; Silvestro, Daniele; Lister, Adrian M.; DelPero, Massimiliano; Riddle, Brett
Abstract Aim Small body size in Madagascar's dwarf and mouse lemurs (Cheirogaleidae) is generally viewed as primitive. We investigated the evolution of body size in this family and in its sister‐taxon, the Lepilemuridae, from phylogenetic, ontogenetic and adaptive perspectives. Location Madagascar. Methods We used a phylogenetic method to reconstruct the evolution of body size in lemurs, and allometric regression models of gestation periods and static and growth allometries in Cheirogaleidae and Lepilemuridae to test the hypothesis that dwarfing occurred as a result of truncated ontogeny (progenesis). We also examined adaptive hypotheses relating body size to environmental variability, life history, seasonality of reproduction, hypothermy (use of torpor), and a diet rich in plant exudates. Results Our results indicated that cheirogaleids experienced at least four independent events of body size reduction from an ancestor as large as living Lepilemuridae, by means of progenesis. Our interpretation is supported by the paedomorphic appearance and parallel ontogenetic trajectories of the dwarf taxa, as well as their very short gestation periods and increased fecundity. Lepilemur species that occupy more predictable environments are significantly larger than those occupying unpredictable habitats. Main conclusions Cheirogaleidae appear to be paedomorphic dwarfs, a consequence of progenesis, probably as an adaptation to high environmental unpredictability. Although the capacity to use hypothermy is related to small body size, this advantage is unlikely to have driven dwarfing in cheirogaleids. We propose that gummmivory/exudativory co‐evolved with body size reduction in this clade, probably from a folivorous ancestor. Their small size is derived, and their suitability as models for the 'ancestral primate' is therefore dubious.